2018
DOI: 10.1016/j.gaitpost.2018.06.173
|View full text |Cite
|
Sign up to set email alerts
|

Carrying asymmetric loads while walking on an uneven surface

Abstract: Background Individuals often carry asymmetric loads over challenging surfaces such as uneven or irregular terrain, which may require a higher demand for postural control than walking on an even surface. Research Question The purpose of this study was to assess postural stability in the medial-lateral (ML) direction while carrying unilateral versus bilateral loads when walking on even versus uneven surfaces. Methods Nineteen healthy young adults walked on even and uneven surface treadmills under three load cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 29 publications
0
25
1
Order By: Relevance
“…ML COP positions, velocities, and accelerations were used to calculate ML TTC using the equation in Figure 2. Since the COP shifts between the boundaries of each foot during walking, a modified version of TTC was utilized (Wang and Gillette, 2018b). In brief, TTC was calculated at each data point and then compared to the remaining single stance time (Figure 3).…”
Section: Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…ML COP positions, velocities, and accelerations were used to calculate ML TTC using the equation in Figure 2. Since the COP shifts between the boundaries of each foot during walking, a modified version of TTC was utilized (Wang and Gillette, 2018b). In brief, TTC was calculated at each data point and then compared to the remaining single stance time (Figure 3).…”
Section: Data Processingmentioning
confidence: 99%
“…Previous studies have reported that an asymmetric load resulted in increased mediolateral (ML) center of pressure (COP) velocity during quiet standing (Anker et al, 2008;Zultowski and Aruin, 2008) and higher ML COP displacement during gait initiation (Fraga et al, 2016) as compared to bilateral loads. More recently, a study has found that asymmetric load carriage with a hand-held bag required more rapid ML postural adjustments as compared to bilateral load carriage during gait (Wang and Gillette, 2018b). However, two studies did not find differences in ML COP parameters between asymmetric and bilateral load carriage during gait (Bampouras and Dewhurst, 2016;Hill et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The great toe transfer is recognized as being able to achieve both esthetic appearance and good function in the reconstructed thumb, while the second toe transfer is thought to result in less donor site morbidity [4]. The current specific considerations regarding the selection of the toe(s) are greatly based on the surgeon's experience and patient's need [5].…”
Section: Introductionmentioning
confidence: 99%
“…The great toe transfer is recognized as being able to achieve both aesthetic appearance and good function in the reconstructed thumb, while the second toe transfer is thought to result in less donor site morbidity [4]. The current speci c considerations regarding the selection of the toe(s) are greatly based on the surgeon's experience and patient's need [5].…”
Section: Introductionmentioning
confidence: 99%